Epidemiology of Frequently Occurring Skin Diseases in Italian Children from 2006 to 2012: A Retrospective, Population‐Based Study. Issue 5 (16th April 2015) - Cantarutti, Anna; Donà, Daniele; Visentin, Federica; Borgia, Eleonora; Scamarcia, Antonio; Cantarutti, Luigi; Peruzzi, Elena; Egan, Colin Gerard; Villa, Marco; Giaquinto, Carlo; Pedianet
Abstract Background Recent estimates indicate an increase in the prevalence of skin diseases in children. Few large epidemiologic studies have examined prevalence trends in Europe. This study evaluated the incidence and prevalence of frequently occurring pediatric skin diseases (PSDs) in Italy as seen by family pediatricians (FPs). Methods Data were retrospectively extracted from the Pedianet database (2006–2012) in children ages 0 to 14 years presenting with a skin disease at their FP. The incidence and prevalence estimates were calculated per year and stratified according to sex, age, and geographic area. Results A mean of 145, 233 children (52.1% male) across five Italian regions were registered with their participating FP for a total of 913, 253 person‐years of follow‐up. The majority of patients were from the northeast (44.6%) and 37.7% were ages 5–9 years. Incidence estimates (new cases/1, 000 person‐years) for most PSDs increased from 2006 to 2012, the highest being for atopic dermatitis (AD) (14.1 vs 16.5), acute urticaria (10.1 vs 11.6), and contact dermatitis (9.3 vs 10.8), whereas psoriasis remained unchanged over the 7 years (0.61 vs 0.57). In contrast, prevalence estimates (cases/100 patients) increased two to three times for several PSDs, including AD (2.7% vs 8.5%), seborrheic dermatitis (0.5% vs 1.6%), chronic urticaria (0.4% vs 0.8%), and psoriasis (0.09% vs 0.22%). Differences in prevalence according to age range and geographic area were observed for psoriasis, AD, and urticaria. Conclusion This study provides comprehensive evidence of the increasing prevalence and incidence of PSDs across Italy. Additional causality studies to address this important clinical and psychosocial problem are recommended.